Link between blood flow and muscle protein metabolism in elderly adults - Hirofumi Zempo; Mitsuaki Isobe; Hisashi Naito (Japanese Society of Physical Fitness and Sports Medicine, 2017)
The mechanism which causes sarcopenia, a loss of muscle mass and strength with aging, remains unclear. Muscle mass is controlled by the net balance between protein synthesis and breakdown; however, net balance differences in the basal state do not contribute to sarcopenia. On the other hand, anabolic resistance, a reduction in muscle protein synthesis in response to protein intake, does seem to be involved in sarcopenia. Muscles which are subject to anabolic resistance do not show incremental blood flow volume during the fed-state. Because the vascular system transports amino acids and other nutrients that are essential for muscle protein synthesis, blood flow volume may be a regulator of anabolic resistance. There is some evidence of a link between blood flow and muscle protein metabolism. In addition, a combination of resistance training and amino acid supplementation promotes a positive net protein balance. Resistance training improves, and detraining reduces blood flow volume; therefore, blood flow volume may be involved as a background mechanism for sarcopenia. Moreover, previous studies have shown that sodium nitroprusside, a vasodilatory nitric oxide donor, enhances muscle protein synthesis. Conversely, angiotensin II, a major vasoconstrictive peptide, induces skeletal muscle protein breakdown. In this review, we discuss a possible role for blood flow in skeletal muscle protein metabolism in elderly adults. The regulation of blood flow may prove to be a beneficial treatment for sarcopenia.